Islanded Microgrid with Decentralized Control for Optimal Generation Dispatch - Khan M.R.B.; Pasupuleti J.; Jidin R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Generally, a centralized energy management system (EMS) has been used for EMS in a microgrid. However, centralized EMS faces challenges in satisfying the adaptability and fault tolerance. Hence, this study proposed decentralized EMS architecture for optimizing the power dispatch of a microgrid consists of distributed generators. The microgrid architecture comprises of loads and distributed generation system. The dispatch from each distributed source, agent-based decentralized EMS structure, has been used for optimizing the power dispatch. The performances of the microgrid system with EMS evaluated through simulations of generation and load side disturbances. Compared to centralized EMS, the Multi Agent System (MAS) based EMS microgrid model capable of providing higher efficiency of power generations with lower power losses. 2020 IEEE.